A new housing class? - Waitkus, Nora (Housing, theory and society, 2025)
This comment argues that the concept of the “zone of precarity” offers a valuable lens for rethinking recent housing class dynamics. Smith and Wood propose that individuals striving to own or fearing they will lose ownership might share common concerns around housing affordability and security - forming a fringe space that reveals complex interactions within contemporary housing classes. While compelling, this space is difficult to empirically locate and may be less prevalent outside liberal housing regimes. Multiple tenure changes are deeply shaped by regime-specific configurations suggesting that this zone of precarity may be not as universal as claimed. Whether this constitutes distinct housing class remains therefore uncertain and yet to be determined. An alternative approach to transcend housing classes is the decommodification of housing, reframing it not as an asset but as an “infrastructure of care”. In this decommodified future, housing would serve social needs rather than market interests, rendering the concept of housing classes less necessary.